Early mobilization of patients with subarachnoid haemorrhage: a national survey of french intensive care units - Adéla Foudhaili; Damien Vitiello; Benjamin Glenn Chosuterman (Medical Journals Sweden, 2024)
Objective: To describe French intensive care unit practices regarding the mobilization of patients with subarachnoid haemorrhage. Design: A cross-sectional nationwide survey study. Subjects: Intensivists and physiotherapists or nurses from French intensive care units managing patients with subarachnoid haemorrhage. Methods: An online questionnaire survey was distributed through the Neurocritical Care and Neuro Anesthesiology French Speaking Society. Results: The response rate was 89%. Of these, 90% did not have a mobilization protocol for patients with subarachnoid haemorrhage. Sixteen percent of departments prohibited all forms of motor physiotherapy for a predefined period. Nineteen percent systematically prohibited out-of-bed mobilization, regardless of the severity of subarachnoid haemorrhage and in the absence of any complication, for a predefined period. The main factors that would delay or interrupt physiotherapy prescription were intracranial hypertension (79%), currently treated vasospasm (59%), and suspicion of vasospasm (44%). Ninety-one percent of the centres identified at least one complication that could be associated with standing upright. These mainly included decreased cerebral perfusion (71%), dislodged external ventricular or lumbar derivations (68%), and haemodynamic instability (65%). Conclusion: Mobilization of patients with subarachnoid haemorrhage is heterogeneous among French neuro-intensive care units and several barriers preclude improvement of mobilization practices. Interventional studies assessing mobilization practices, as well as education and training of staff, are crucial to ensure the proper management of patients with subarachnoid haemorrhage and to improve outcomes.